Health and Social Care Systems of the Future: Demographic Changes, Digital Age and Human Factors Proceedings of the Healthcare Ergonomics and Patient Safety, HEPS, 3-5 July, 2019 Lisbon, Portugal - Cotrim, Teresa Patrone; Serranheira, Florentino; Sousa, Paulo; Hignett, Sue.; Albolino, Sara.; Tartaglia, Riccardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses how digital technology and demographic changes are transforming the patient experience, services, provision, and planning of health and social care. It presents innovative ergonomics research and human factors approaches to improving safety, working conditions and quality of life for both patients and healthcare workers. Personalized medicine, mobile and wearable technologies, and the greater availability of health data are discussed, together with challenges and evidence-based practice. Based on the Healthcare Ergonomics and Patient Safety conference, HEPS2019, held on July 3-5, 2019, in Lisbon, Portugal, this book offers a timely resource for graduate students and researchers, as well as for healthcare professionals managing service provision, planners and designers for healthcare buildings and environments, and international healthcare organizations.
Taking Forward Human Factors and Ergonomics Integration in NHS Scotland: Progress and Challenges -- Human Centric Lighting, a new reality in healthcare environments -- Alarm response in critical care: Obstacles for compliance -- Improving ergonomics competences in the social and health care sector in Finland -- Prevalence assessment of musculoskeletal and visual symptoms among pathological anatomy service workers -- Leveraging antimicrobial stewardship: focus on individual prescriptions appropriateness -- Assessment of azole resistance in clinical settings by passive sampling -- Cognitive Ergonomics 'Features' as a Tool for Designing Interaction with Medical Devices -- A Serious Game to promote compliance with hand hygiene among Healthcare Workers: Results from User Research stage.
Keywords: Computational intelligence; Medical informatics; Occupational health services; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Health Informatics; Occupational Health; User Interfaces and Human Computer Interaction